Optimization of Operational Parameters to Enhance Ultrafiltration Efficiency Using Dairy Wastewater Model - Aws Altayawi; Hajnalka Csott; Zsuzsanna Horváth Hovorka; István Hatos; Zsuzsanna László; Gábor Veréb; Maravic Nikola; Zita Šereš; Szabolcs Kertész (Analecta)
Ultrafiltration is a key technology for treating dairy wastewater; however, its efficiency is often hindered by critical challenes such as membrane fouling and concentration polarization. To mitigate these issues, one effective approach involves optimizing operational parameters to enhance system performance and longevity. In this study the influence of key operational parameters on the performance of a lab-scale low-pressure ultrafiltration membrane system for treating dairy wastewater model were investigated. The optimization focused on three critical factors: transmembrane pressure (TMP), stirring speed, and membrane molecular weight cut-off (MWCO). Key performance metrics, including permeate flux, membrane retention efficiency, and total, reversible, and irreversible membrane resistances, were analyzed. The results showed that the optimal conditions were identified using a 20 kDa polyethersulfone membrane, with a TMP of 0.3 MPa and a stirring speed of 400 rpm. Statistical analysis was conducted to further refine and validate the optimization of these parameters.